Validation of sleep stage classification using non-contact radar technology and machine learning (Somnofy®) - Toften, S.; Pallesen, S.; Hrozanova, M.; Moen, F.; Grønli, J. (Sleep Medicine, 2020)
Radar technology/machine learning (Somnofy®) were validated against polysomnography. In healthy adults, Somnofy® detected sleep/wake correctly 0.97 and 0.72 of the time. Sleep stage differentiation showed substantial agreement with polysomnography. TST and SE exhibited excellent and good reliability compared to polysomnography.